2004
DOI: 10.3171/ped.2004.100.5.0473
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial midline dermoid and epidermoid cysts in children

Abstract: Because surgery is the only effective treatment modality for these lesions, radical resection should be performed in all cases to avoid tumor recurrence; however, because the cyst capsule can adhere firmly to vital structures and attempts at its radical removal can be dangerous, subtotal resection may be a wise option in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 28 publications
0
78
0
3
Order By: Relevance
“…Because of their slow rate of growth, intracranial dermoid cysts are rarely discovered during infancy. 6 One study reported a mean age of 15 years at the time of diagnosis, 11 whereas other studies have documented the most common presentation with symptoms in the 3rd or 4th decade of life. 8,9,21,27 Despite their benign nature, dermoid cysts may result in serious CNS complications, such as progressive symptoms related to local mass effect, septic or aseptic meningitis, obstructive hydrocephalus, or intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of their slow rate of growth, intracranial dermoid cysts are rarely discovered during infancy. 6 One study reported a mean age of 15 years at the time of diagnosis, 11 whereas other studies have documented the most common presentation with symptoms in the 3rd or 4th decade of life. 8,9,21,27 Despite their benign nature, dermoid cysts may result in serious CNS complications, such as progressive symptoms related to local mass effect, septic or aseptic meningitis, obstructive hydrocephalus, or intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, dermoid cysts should be resected early at the time of diagnosis before they involve surrounding neural or vascular tissue, even in patients lacking neurological symptoms. 6,14 In this case report, the posterior fossa dermoid cyst considerably increased in size in the span of 2.5 years. The cyst was attached to a cutaneous dermoid sinus tract and extended in the midline all the way to the fourth ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their congenital origin, these tumors typically arise between infancy and young adulthood (2). They are considered likely to arise from a defective neural tube closure, which occurs between the third and fifth weeks of gestation (2).…”
Section: Introductionmentioning
confidence: 99%